Spatial distribution of landslide potentials and landslide vulnerability in Sukawana and Awan Villages, Kintamani District, Bangli Regency, Bali Province - Made Sri Sumarniasih; I Gusti Ayu Sintya Dewi; I Wayan Diara (Brawijaya University, 2023)
Landslide is one of the disasters that often occurs in Indonesia. Bangli is one of the areas in Bali with a high potential for landslides, especially in Kintamani. This study aimed to identify the potential and vulnerability of landslides in Sukawana and Awan Villages, Kintamani District, Bangli Regency. This study used survey and scoring methods according to the Natural Disaster Center at Gadjah Mada University for the parameters that cause landslides, namely, landform, rainfall, slope, geological structure, land use, and soil type. The landslide potential in Sukawana Village is low landslide potential with an area of 71.97 ha (1.81%) in Banjar Kubusalya, a medium potential with an area of 2,198.07 ha (55.30%) in Banjar Kubusalya, Banjar Sukawana and Banjar Paketan and high potential with an area of 932.81 ha (23.47%) located in Banjar Kuum and Banjar Sukawana. Awan Village has medium potential with an area of 772.20 ha (19.43%). For areas with high vulnerability, settlements are 110.96 ha (69.97%) in Sukawana Village, and the road network is dominated by local roads along 28.82 km (34.81%), which are in Sukawana Village.